Movement pattern and physiological response in recreational small-sided football – effect of number of players with a fixed pitch size. Issue 13 (3rd July 2018) - Randers, Morten B.; Ørntoft, Christina; Hagman, Marie; Nielsen, Jens J.; Krustrup, Peter
ABSTRACT: Recreational soccer is an effective health-promoting activity, but it is unclear how different game formats influence internal and external load. Thus, to be able to advise how to maximise the outcome of recreational football, we examined movement pattern and physiological response in 11 untrained men (32.6 ± 6.7 yrs, 23.3 ± 4.9 fat%, 43.4 ± 5.3 ml·min −1 ·kg −1 ) during three football sessions comprising 4 × 12 min of 3v3, 5v5 or 7v7 with a constant pitch size of 20 × 40 m. Movement pattern, heart rate (HR), blood lactate and RPE were measured during and after the 12-min periods. Greater (P < 0.05) total distance and high-speed distance was covered during 3v3 than 5v5 (14 and 30%) and 7v7 (15 and 75%). Mean HR was higher in 3v3 (85.7 ± 5.7%HRmax) and 5v5 (84.2 ± 5.1%HRmax) than in 7v7 (80.7 ± 4.6%HRmax, P < 0.05) and percentage time >90%HR was higher in 3v3 (43 ± 18%, P < 0.05) than in 5v5 (28 ± 21%) and 7v7 (18 ± 14%). Blood lactate was higher in 3v3 (7.4 ± 2.7 mmol·l −1 ) than in 7v7 (4.5 ± 2.2 mmol·l −1, P < 0.001) but not in 5v5 (6.1 ± 2.1 mmol·l −1, P = 0.061). RPE was higher in 3v3 (6.7 ± 2.3, P < 0.01) than in 5v5 (5.2 ± 2.2) and 7v7 (4.3 ± 2.3). In conclusion, higher external and internal load was found with fewer players, when the pitch size is fixed.